PENGARUH MODEL PEMBELAJARAN PROBLEM BASSED LEARNING BERBANTUAN ALAT PERAGA KONTEKSTUAL TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPAS DI KELAS IV SDK MARIA FERRARI - Enjeli Ure Hayon, Sisilia; Ehe Lawotan, Yohanes; Hero, Hermus (Jurnal Biogenerasi, 2024)
The purpose of this research is to determine the effect of the Problem-Based Learning (PBL) model assisted by contextual teaching aids on the science learning outcomes of Class IV A students at SDK Maria Ferrari. The population of this study consists of 31 students in Class IV A at SDK Maria Ferrari. This study employs a pre-experimental research design with a one-group pretest and posttest approach, using non-probability sampling for sample selection. Data collection techniques include observation and tests. The results of the study indicate that the use of the Problem-Based Learning model assisted by contextual teaching aids has a significant impact, as demonstrated by hypothesis testing. It can be concluded that the use of the Problem-Based Learning model assisted by contextual teaching aids can improve the learning outcomes in the topic of energy transformation for Class IV A students at SDK Maria Ferrari, Maumere.